2001
DOI: 10.1103/physrevb.64.020407
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic excitations in a nanocontact

Abstract: The domain wall in a ferromagnetic nanocontact adopts a specific configuration-Néel-like, vortex, or Bloch-like-depending on the dipole-dipole interactions governed by the size and shape of the contact and its atomic structure. Spontaneous thermal fluctuations between these modes arise in a soft ferromagnet at room temperature when the dimensions of the contact are less than about 10 nm. The giant magnetoresistance of a nanocontact may be reduced, but not eliminated by the mode fluctuations. DOI: 10.1103/PhysR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 11 publications
2
25
1
Order By: Relevance
“…Monte Carlo simulations of the magnetisation in nanocontacts confirm Bruno's idea of a constrained wall and showed the possibility of thermal fluctuations in the form of walls in a nanocontact between various different Bloch, Néel, and vortex states [331]. They estimate the height of the energy barrier separating these states as equivalent to about 80 mK per atom, meaning that structures smaller than about 10 nm in size will be unstable at room temperature [332]. This opens a new inelastic scattering mechanism in the contact, which can break phase, flip spins and otherwise reduce the magnetoresistance of a contact.…”
Section: Theoretical Interpretationmentioning
confidence: 69%
“…Monte Carlo simulations of the magnetisation in nanocontacts confirm Bruno's idea of a constrained wall and showed the possibility of thermal fluctuations in the form of walls in a nanocontact between various different Bloch, Néel, and vortex states [331]. They estimate the height of the energy barrier separating these states as equivalent to about 80 mK per atom, meaning that structures smaller than about 10 nm in size will be unstable at room temperature [332]. This opens a new inelastic scattering mechanism in the contact, which can break phase, flip spins and otherwise reduce the magnetoresistance of a contact.…”
Section: Theoretical Interpretationmentioning
confidence: 69%
“…Another issue is that thermally activated fluctuations between different magnetic modes are to be expected in constrictions smaller than about 10 nm at room temperature. 27 In conclusion, the sharp low-field feature in the resistance of nickel nanocontacts has been attributed to ballistic magnetoresistance. The smallness of the effect ͑Ϸ1%͒ in Ohmic or in tunnel-barrier contacts reflects the fact that dipolar interactions tend to impose an antiparallel spin alignment across the contact, which is little influenced by the magnetization direction of the electrodes.…”
Section: ͑Nm͒ ͑2͒mentioning
confidence: 83%
“…24 While this model is certainly oversimplified, it can explain why no huge ballistic magnetoresistance is observed in this type of contact. Atomic Monte Carlo 25 and micromagnetic 26,27 simulations of different nanocontacts and nanoconstrictions indicate that there are vortex modes in small constrictions. Our own OOMMF simulations ͑Fig.…”
Section: ͑Nm͒ ͑2͒mentioning
confidence: 96%
“…Coey et al concluded [29,30] that giant MR of a nanocontact may be reduced somewhat by these fluctuations, but not eliminated. In recent calculations Zhuravlev et al [31] also predicted giant values and fluctuations of MR in segmented nanowires, when conductance of the wire is quantizes.…”
Section: Discussion Of the Resultsmentioning
confidence: 99%